Embodying Historical Learners' Messages as Learning Companions in a VR Classroom - Liao, Meng-Yun; Sung, Ching-Ying; Wang, Hao-Chuan; Lin, Wen-Chieh; Cherng, Fu-Yin (My University, 2019)
Online learning platforms such as MOOCs have been prevalent sources of self-paced learning to people nowadays. However, the lack of peer accompaniment and social interaction may increase learners' sense of isolation. Prior studies have shown the positive effects on visualizing peer students' appearances in VR learning environments. In this work, we propose to build virtual classmates, which were constructed by synthesizing previous learners' time-anchored messages. Configurations of virtual classmates and their behavioral features can be adjusted. To build the characteristics of virtual classmates, we developed a technique called comment mapping to aggregate prior online learners' comments to shape virtual classmates' behaviors. We evaluated the effects of the virtual classmates built with and without the comment mapping and the amount of virtual classmates rendered in VR.
Keywords: Online Learning; VR Classroom; Virtual Classmates